Assessment of everyday executive functioning using the BRIEF in children and adolescents treated for brain tumor. (20th March 2020) - Roche, Jeanne; Câmara-Costa, Hugo; Roulin, Jean-Luc; Chevignard, Mathilde; Frappaz, Didier; Guichardet, Karine; Benkhaled, Ouarda; Kerrouche, Bernadette; Prodhomme, Julie; Kieffer-Renaux, Virginie; Le Gall, Didier; Fournet, Nathalie; et al.
ABSTRACT: Objective : Childhood brain tumors (BTs) and their treatment often negatively affect development of executive functions. Previous studies have reported executive functions deficits, particularly through questionnaires of daily life. This study aimed to assess executive functioning in everyday life following pediatric BT, in a larger and more histologically diverse sample than previously, and to study clinical and demographic factors influencing outcome. Methods : Assessment of executive functioning using parent ratings of the Behavior Rating Inventory of Executive Function (BRIEF), in a large sample of children treated for various BT (n = 153). Clinical and demographic factors were: age at diagnostic, age at assessment, parental education level, radiation therapy. Results : Significant difficulties were found in the 3 composite indices and in the majority of the BRIEF subscales. The highest level of difficulties was observed in the Working Memory subscale. Older age at assessment and younger age at diagnosis were significantly associated with higher levels of parent-reported difficulties, particularly for metacognition. Conclusions : Parents of children treated for BT report widespread and persistent deficits in executive functions that negatively affect their everyday functioning. Including analysis of all clinical scales and composite indices allows a more comprehensive approach and enables to specify the patients' executive profile.